Colloidal gold-based immunochromatographic strip assay for the rapid detection of three natural estrogens in milk. (1st September 2018) - Wang, Zhongxing; Guo, Lingling; Liu, Liqiang; Kuang, Hua; Xu, Chuanlai
Highlights: A rapid colloidal gold-based immunoassay strip assay was developed for the determination of E1, 17β-E2, and E3 residues in milk samples. The assay had a low detection limit, and required a short time. The results obtained from the immunochromatographic strip assay were consistent with those obtained from ic-ELISA and gas chromatography–mass spectrometry. Abstract: In this study, we developed highly sensitive and specific monoclonal antibodies (mAbs) against estrone (E1 ), 17β-estradiol (17β-E2 ), and estriol (E3 ). The half-maximal inhibitory concentration values of anti-E1, anti-17β-E2, and anti-E3 mAbs were 0.46, 0.36, and 0.39 ng/mL, respectively, based on competitive enzyme-linked immunosorbent assay (ic-ELISA) results. A rapid colloidal gold-based immunoassay strip assay was developed for the determination of E1, 17β-E2, and E3 residues in milk samples. The assay had a visual cut-off value of 5 ng/mL, and required 10 min to assess with the naked eye. The results obtained from the immunochromatographic strip assay were consistent with those obtained from ic-ELISA and gas chromatography–mass spectrometry. The immunochromatographic strip assay is useful and rapid for the detection of E1, 17β-E2, and E3 in milk.